Work‐related musculoskeletal disorders and associated risk factors among urban metropolitan hairdressers in India. Issue 1 (15th February 2021) - Mishra, SukhDev; Sarkar, Kamalesh
Abstract: Objectives: Ergonomic hazards account for a substantial proportion of work‐related diseases and injuries among hairdressers. Awkward posture during work, repetitive movements, prolonged standing, and long working periods to carry out work activities cause mechanical load on the joints and work‐related musculoskeletal disorders (WMSDs). This study investigated the musculoskeletal problems among urban hairdressers and associated risk factors. Methods: This study investigates the prevalence of WMSDs among 768 study subjects (384 hairdressers and control subjects each) from Ahmedabad and New Delhi metropolis in India. Univariate statistical analysis was carried out along with 95% confidence interval for effect estimates. Results: Findings reveal that the nearly half of the hairdressers suffered from knee and foot pain (49.5%), followed by lower back pain (39.8%) and upper back pain (38.8%). The neck pain and shoulder pain were reported by more than 25% hairdressers. The odds of developing neck pain (OR = 2.04; 95% CI 1.37‐3.06) and shoulder pain (OR = 1.85; 95% CI 1.25‐2.73) were significantly higher than control. The female hairdressers were more likely to experience work‐related musculoskeletal disorder (OR = 2.63; 95% CI 1.18‐5.86) than male counterparts. Hairdressers within the age of 18‐35 years had significantly higher occurrence of musculoskeletal disorders with longer duration of working hours at the workplace. Longer daily work hours (>12 hours) posed significantly higher risk (OR = 2.47; 95% CI 1.39‐4.38) of experiencing MSD for hairdressers. Conclusion: A very large proportion of hairdressers suffered with work‐related musculoskeletal disorders. The long daily working hours and gender of the hairdresser are associated with increased risk of developing WMSDs.